Status Rumah Ibadah Dalam Pertimbangan Hakim Berkaitan Dengan Gugatan Sengketa Kepemilikan Bangunan Gereja - Paraou Paskalis Sitanggang (Comprehensive Law Journal, 2024)
Worship house is a building that functions as a place of worship established by members of a religion. From the beginning onwards, places of worship will always be used as a gathering place for the community to study religious values as well as being a marker (symbol) of the practice of religious teachings in living together in society. In short, houses of worship are present in society with social motives. On the other hand, other buildings, for example shops, warehouses, factories, hotels and so on, are buildings whose function and purpose are economically motivated, namely buildings with the aim of making a profit because they are used for business purposes. The probles in this research are whether the status of a church that functions as a house of worship can be a note that the judge takes into account when considering decisions and whether the status of a church that functions as a house of worship can prevent negative court decisions from occurring. This research uses normative legal research methods and the results of this research are that the status of a church that functions as a place of worship is not a note that the judge takes into account when considering the decision. Furthermore, the status of the church as a home is also not sufficient to prevent negative court decisions.